Dietary isobutyric acid supplementation improves intestinal mucosal barrier function and meat quality by regulating cecal microbiota and serum metabolites in weaned piglets - Wang, Binjie; Hou, Junjie; Cao, Yundong; Wei, Haibo; Sun, Kangle; Ji, Xiang; Chu, Xiaoran; Zhang, Yu; Jiang, Sen; Shi, Linlin; Liu, Ke; Song, Zhen; et al. (Frontiers in Veterinary Science, 2025)
This study aimed to provide evidence for the effects of isobutyric acid on the intestinal mucosal barrier and gut microbiota in weaned piglets. In this study, 30 piglets were divided into two groups: one group was fed a standard diet (CON group), and the other group was fed a diet supplemented with 0.5% isobutyric acid (IB group) for 21 days. The results showed that isobutyric acid significantly increased (p < 0.05) serum immunity and antioxidant capacity in weaned piglets. In small intestine of piglets, the ratio of villus height to crypt depth was significantly increased (p < 0.05). Administration of isobutyric acid also increased (p < 0.05) the expression of genes related to intestinal mucosal barrier function. Cecal microbiota analysis revealed that isobutyric acid significantly increased (p < 0.05) the abundance of the Eubacterium coprostanoligenes group. Untargeted serum metabolomics analysis indicated that the top three categories of metabolites were lipids and lipid-like molecules, organic acids and derivatives, and organic heterocyclic compounds. Additionally, in longissimus thoracis muscle, isobutyric acid significantly increased (p < 0 0.05) intramuscular fat and triglyceride content compared with the CON group. Overall, isobutyric acid can improve small intestinal mucosal barrier function, and may influence the fat deposition through the regulation of serum metabolites in weaned piglets.